Revolutionizing Automation Testing with AI: A New Era of Intelligent Quality Assurance - Priya Yesare, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Automation testing using AI is replacing the conventional testing procedures by optimizing efficiency, accuracy and defect detection. Traditional automation testing is based on the scripts but the prediction of analytics and machine learning is used in AI powered framework to optimize the test execution. The focus of this research is the effects that AI driven automation has for defect leakage reduction, test maintenance cost reduction, and adaptability. The leakage rate defect reduction is found to be 66%, while the cost reduction is 60%. Integration of AI into testing frameworks help organizations speed up the releases, provide higher test coverage and enhanced software reliability. The study also highlights the importance of AI in the future of the software testing.
Keywords: AI; Quality; Intelligent; Assurance